EFEKTIVITAS PROGRAM PROYEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) TERHADAP KREATIVITAS PESERTA DIDIK (STUDI SURVEY DI SMA PELITA TIGA JAKARTA) - Nadiah; Dian Safitri Aminanti (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2024)
The Pancasila Student Profile Strengthening (P5) Project Programme activities in each school are mandatory for students to participate in. With this P5 project activity, students can hone their psychomotor skills and increase creativity in learning. The purpose of the study is to understand the effectiveness of the P5 strategy on the creativity of Pelita Tiga Jakarta High School students. The research method uses quantitative correlation method. Simple random selection was used to draw a sample of 34 students. Data were obtained through interviews and observations and evaluated using product moment correlation technique. The results obtained 0.677 > 0.344 / 0.442 (sig level 5% or 1%). So it is concluded that the effectiveness of the Pancasila student profile project programme (P5) has an influence or impact to increase student creativity at SMA Pelita Tiga Jakarta